Antihypertensive Drug Prescribing Pattern at Pharmacy X Yogyakarta - Claudia Atiameru, Shintia; Hardiyanto Soegiantoro, Didiek; Puspita Atmaja, Sarah (Sean Institute, 2023)
Hypertensive patients who have seen a doctor at primary or advanced health facilities generally get a doctor's prescription. On the antihypertensive drug prescription sheet, information can be obtained about the pattern of prescribing antihypertensive drugs such as the classification of antihypertensive drugs used for patient treatment and gender characteristics of hypertensive patients. This study aims to describe the characteristics of hypertensive patients and the types of antihypertensive drugs prescribed by doctors and purchased at Pharmacy X Yogyakarta. The research method used was a retrospective quantitative descriptive study using a sample of the entire population of prescriptions containing antihypertensive drugs during January to June 2023. The results of the study found that the number of prescriptions containing antihypertensive drugs at Pharmacy X Yogyakarta fluctuated between 3 to 10, with the gender characteristics of patients balanced between men and women. The types of antihypertensive drugs that patients buy every month with a doctor's prescription are the most cardioselective beta blockers, ARBs, and CCBs of dihydropyridine